1995
DOI: 10.1007/bf00318567
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes of anterior horn neurons and their synaptic input caudal to a low thoracic spinal cord hemisection in the adult rat: a light and electron microscopic study

Abstract: Structural changes in lumbosacral ventral horn neurons and their synaptic input were studied at 3, 10, 21, 42, and 90 days following low thoracic cord hemisection in adult rats by light microscopic examination of synaptophysin immunoreactivity (SYN-IR) and by electron microscopy. There was an ipsilateral transient decrease in SYN-IR at the somal and proximal dendritic surfaces of anterior horn neurons which extended caudally from the site of injury over a postoperative (p.o.) period of 42 days. Concomitantly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 64 publications
2
30
0
1
Order By: Relevance
“…The abnormalities found in the intact spinal cord may contribute to motor impairments of TNR Ϫ/Ϫ mice that become apparent under demanding conditions, such as rotarod, pole, and wirehanging tests (Freitag et al, 2003), but are not detectable in less stressful and challenging tests as those used here for analysis of motor functions. Previous studies have shown that spinal cord injury causes an acute loss of motoneuron perisomatic terminals, which is gradually reversed in chronic paraplegic rats (Nacimiento et al, 1995). In wild-type mice studied 6 weeks after injury, densities of GABAergic terminals were similar to intact mice, suggesting that this local input is not changed after injury or is normalized during the recovery period.…”
Section: Enhanced Recovery In Tnr-deficient Micementioning
confidence: 68%
“…The abnormalities found in the intact spinal cord may contribute to motor impairments of TNR Ϫ/Ϫ mice that become apparent under demanding conditions, such as rotarod, pole, and wirehanging tests (Freitag et al, 2003), but are not detectable in less stressful and challenging tests as those used here for analysis of motor functions. Previous studies have shown that spinal cord injury causes an acute loss of motoneuron perisomatic terminals, which is gradually reversed in chronic paraplegic rats (Nacimiento et al, 1995). In wild-type mice studied 6 weeks after injury, densities of GABAergic terminals were similar to intact mice, suggesting that this local input is not changed after injury or is normalized during the recovery period.…”
Section: Enhanced Recovery In Tnr-deficient Micementioning
confidence: 68%
“…These studies indicate that physiological, biochemical, and functional reorganization of lumbar spinal cord occur over time (Nacimiento et al, 1995;Edgerton et al, 1997a,b;Giroux et al, 1999). Consistent with this, strategies to recover motor functions after spinal cord injury (SCI) include the management of sublesional spinal cord based on the reorganization of the remaining undamaged neural pathways.…”
Section: Introductionmentioning
confidence: 90%
“…47,48 We performed a systematic analysis of the immunostaining for synaptophysin in the cervical spinal cord (C4-C8) as a first step in characterizing the synaptic changes that occur in the partially denervated segments. Our objective was to investigate the possibility that synaptic loss persisted chronically in the spinal cord segments adjacent to the lesion site and, hence, we quantified the intensity of staining in a group of normal rats (n = 8) and two groups of rats with C6 hemisection, at 30 (n = 12) or 90 (n = 12) DPI.…”
Section: Synaptophysin Immunohistochemistry and Quantificationmentioning
confidence: 99%